Respostas
respondido por:
1
Resposta:
a) f(2)= 3.2.(-5)
f(2)= -30
b) f(-3)= 3.(-3).(-5)
f(-3)= 45
c) f(0)= 3.0.(-5)
f(0)= 0
d) f(-6)= 3.(-6).(-5)
f(-6)= 90
Explicação passo-a-passo:
espero ter ajudado
respondido por:
1
Resposta:olá espero ajudar nos seus estudos
Explicação passo a passo:
a) f(2)= 3.2.(-5)
f(2)= -30
b) f(-3)= 3.(-3).(-5)
f(-3)= 45
c) f(0)= 3.0.(-5)
f(0)= 0
d) f(-6)= 3.(-6).(-5)
f(-6)= 90
Perguntas similares
3 anos atrás
3 anos atrás
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás